STRUCTURE AND COMPOSITION OF DODECANE LAYERS SPREAD ON AQUEOUS-SOLUTIONS OF DODECYL-AND HEXADECYLTRIMETHYLAMMONIUM BROMIDES STUDIED BY NEUTRON REFLECTION - Lu, J; Thomas, R; Binks, B; Fletcher, P; Penfold, J (1995)
Neutron reflection measurements have been used to study the composition and structure of mixed dodecane-surfactant monolayers at the air/water surface. The surfactants were dodecyltrimethylammonium bromide (C12TAB) and the corresponding C16TAB. Partially isotopically labeled C16TABs were used to localize the position of the oil in the layer with greater precision. The surfactant concentrations were chosen to be at their critical micelle concentrations (cmc) of 14 × 10-3 M (C12TAB) and 9.1 × 10-4 M (C16TAB). The area per molecule for both surfactants increased on the addition of oil from 48 to 54 ± 3 Å2 for C12TAB and 43 to 52 ± 3 Å2 for C16TAB. In each case the surfactant layer was found to be slightly thicker in the presence of dodecane than in its absence, although the increase in area would normally cause the thickness to decrease. The area per molecule of the dodecane was found to be 76 and 67 ± 7 Å2 on C12TAB and C16TAB, respectively, to be compared with earlier surface tension estimates of 78 and 56 Å2. On C12TAB the thickness of the dodecane layer is slightly greater (18.5 ± 2 Å) than its fully extended chain length of dodecane (18 Å), but on C16TAB it is significantly greater (20.5 ± 2 Å). The separations of the centers of the surfactant and dodecane distributions at the corresponding cmc's were found to be 6.5 and 8.5 ± 1 Å. Labeling of the C6 fragments at either end of the C16TAB made it possible to locate the oil distribution more accurately. The center of the outer C6 (hexyl) group (i.e., the air side) of the surfactant tail was found to coincide exactly with the center of the oil distribution, whereas the inner C6 (hexamethylene) group was centered 8.5 ± 1 Å from the center of the oil distribution. © 1995 American Chemical Society.